Early-Onset Colorectal Adenocarcinoma in the IDEA Database: Treatment Adherence, Toxicities, and Outcomes With 3 and 6 Months of Adjuvant Fluoropyrimidine and Oxaliplatin. Issue 36 (20th December 2021) - Fontana, Elisa; Meyers, Jeff; Sobrero, Alberto; Iveson, Timothy; Shields, Anthony F.; Taieb, Julien; Yoshino, Takayuki; Souglakos, Ioannis; Smyth, Elizabeth C.; Lordick, Florian; Moehler, Markus; Giraut, Anne; et al.
Abstract : PURPOSE: Early-onset (EO) colorectal cancer (CRC, age < 50 years) incidence is increasing. Decisions on optimal adjuvant therapy should consider treatment adherence, adverse events, and expected outcomes in a population with life expectancy longer than later-onset (LO) CRC (age ≥ 50 years). MATERIALS AND METHODS: Individual patient data from six trials in the International Duration Evaluation of Adjuvant Chemotherapy database were analyzed. Characteristics, treatment adherence, and adverse events in stage II or III EO-CRC and LO-CRC were compared. To reduce confounders of non–cancer-related deaths because of age or comorbidities, time to recurrence (3-year relapse-free rate) and cancer-specific survival (5-year cancer-specific mortality rate) were considered. RESULTS: Out of 16, 349 patients, 1, 564 (9.6%) had EO-CRC. Compared with LO-CRC, EO-CRC had better performance status (86% v 80%, P < .01), similar T stage (% T1-3/T4: 76/24 v 77/23, P = .97), higher N2 disease rate (24% v 22%, P < .01), more likely to complete the planned treatment duration (83.2% v 78.2%, P < .01), and received a higher treatment dose intensity, especially with 6-month regimens. Gastrointestinal toxicity was more common in EO-CRC; hematologic toxicity was more frequent in LO-CRC. Compared with LO-CRC, significantly worse cancer-specific outcomes were demonstrated especially in high-risk stage III EO-CRC: lower 3-year relapse-free rate (54% v 65%; hazard ratio [HR] 1.33; 95% CI, 1.14 to 1.55; P value < .001) and higher 5-year cancer-specific mortality rate (24% v 20%; HR 1.21; 95% CI, 1.00 to 1.47; P value < .06). In this subgroup, no difference was observed with 3 or 6 months of therapy, with equally poor disease-free survival rates (57% v 56%; HR 0.97; 95% CI, 0.73 to 1.29; P value = .85). CONCLUSION: Young age is negatively prognostic in high-risk stage III CRC and associated with significantly higher relapse rate; this is despite better treatment adherence and higher administered treatment intensity, suggesting more aggressive disease biology. Abstract :